Impact of the consequences of the genocide in Darfur on its victims and the level of condemnation of the crime - Sharafian N. G. (Interactive science, 2019)
genocide in Darfur is one of the most terrible crimes committed against humanity in the 21st century, that forced approximately one-third of the population of the territory to leave their homes and move to refugee camps. The author states, that the consequences were disastrous both for Darfur and its victims. The article renders main consequences of the catastrophic crime against the people of Darfur, analyzes drawbacks of Sudan juridical system and the level of condemnation of the crime.
Keywords: преступность; геноцид; Земля; беженцы; этнические группы; доказательство; refugees; обвинение; proof; голод; Дарфур; Судан; Darfur; Sudan; ethnic groups; hunger; accusation